Religion, Medicine and the Human Embryo in Tibet, by Frances Garrett - Hofer, Theresia (Religions of South Asia, 2010)
Religion, Medicine and the Human Embryo in Tibet, by Frances Garrett. Critical Studies in Buddhism; London and New York: Routledge, 2008. pp. 208, 150.00 (hb). ISBN 978-0-415-44115-5.